ANALISIS FAKTOR KUALITAS PELAYANAN DAN KEPUASAN MAHASISWA TERHADAP MINAT UNTUK MEREFERENSIKAN POLITEKNIK LP3I JAKARTA - KAMPUS BEKASI - Rosita, Rahmi (L2Dikti Wilayah III, 2017)
College education providers should improve service quality, so with a good quality of service they can give satisfaction to the customer in this case students. The purpose of this study is to: (1) describe the quality of service and the satisfaction of students of the Polytechnic Campus in East France, (2) analyze the magnitude of influence. service quality, satisfaction of Student interest refer France Polytechnic Campus in Bekasi (Campus The purpose of this study: 1) to describe the quality of service and satisfaction LP3I Polytechnic Campus Student Bekasi. 2). To analyzethe influence of service quality, student satisfaction referring to interest at the Polytechnic Campus Campus LP3I Bekasi, 3). To analyze which factors have a dominant influence on campus interest Politeknik LP3I Jakarta Campus Bekasi. The research method using multiple linear regrersi, kind research using quantitative and qualitative measurement scale with a Likert scale. Polytechnic student population is LP3I Bekasi Jakarta Campus with a sample of 100 questionnaires that can be analyzed further. Analysis methods such as statistic analysis assisted management with SPSS. From the research, the numbers obtained correlation (R) between quality of service (X1), customers at is faction (X2), there ference interest (Y) is equal to 0836. that is, the relationship between the two variables is very strong. The positive correlation indicates the relationship between service quality, student satisfaction with the direction of there ference interest. To determine the influence of service quality, customer satisfaction, then visits his R Square. Figures R Square is also called the coefficient of determination.